2007
DOI: 10.1161/circulationaha.106.658948
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Cardiovascular Disease Burden Due to Diabetes Mellitus

Abstract: Background-Marked reductions in cardiovascular disease (CVD) morbidity and mortality have occurred in the UnitedStates over the last 50 years. We tested the hypothesis that the relative burden of CVD attributable to diabetes mellitus (DM) has increased over the past 5 decades. Methods and Results-Participants aged 45 to 64 years from the Framingham Heart Study, who attended examinations in an "early" time period (1952 to 1974), were compared with those who attended examinations in a later time period (1975 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
377
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 588 publications
(392 citation statements)
references
References 40 publications
(29 reference statements)
11
377
0
4
Order By: Relevance
“…Diabetes is a serious chronic disease that is growing rapidly in prevalence and that now affects >10% of adults in developed countries [1,2]. People with type 2 diabetes are two to four times more likely to develop a serious cardiovascular outcome compared with those without diabetes [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is a serious chronic disease that is growing rapidly in prevalence and that now affects >10% of adults in developed countries [1,2]. People with type 2 diabetes are two to four times more likely to develop a serious cardiovascular outcome compared with those without diabetes [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…5,7,8 Furthermore, the prevalence of glucose intolerance and obesity has increased greatly in recent years. 9,10 Diabetes mellitus (DM) has become a major public health problem 11,12 as well as a risk factor for all-cause mortality 11 and CVD. 10,[13][14][15] Recently, prediabetic hyperglycemia has been recognized to confer an increased risk for CVD.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Diabetes mellitus (DM) has become a major public health problem 11,12 as well as a risk factor for all-cause mortality 11 and CVD. 10,[13][14][15] Recently, prediabetic hyperglycemia has been recognized to confer an increased risk for CVD. 16 However, a few population studies 17 have reported a positive association between CVD and impaired fasting glucose (defined as blood glucose of 5.6-6.9 mmol l À1 according to the 2003 American Diabetes Association definition).…”
Section: Introductionmentioning
confidence: 99%
“…5 Although the prevalence of cardiovascular disease has declined progressively in the general population, the higher relative risk for cardiovascular disease in people with T2DM has not changed over the last 50 years. 6 It would therefore be advantageous if new glucose-lowering medications could reduce cardiovascular risk, in addition to improving glycemic control.…”
Section: Introductionmentioning
confidence: 99%